2020
DOI: 10.1177/0363546520956266
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Isolated Acute Anterior Cruciate Ligament Reconstruction Are Inferior in Patients With an Associated Anterolateral Ligament Injury

Abstract: Background: Isolated reconstruction of the anterior cruciate ligament (ACL) does not reestablish the normal knee biomechanics in cases of associated injuries to the anterolateral structures. Studies evaluating the potential clinical effect of anterolateral ligament (ALL) injury on the treatment of ACL injuries are necessary to validate the findings of biomechanical studies. Purpose: To evaluate the clinical outcomes and failure rate of ACL reconstruction in patients with and without ALL injury diagnosed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 36 publications
1
38
0
5
Order By: Relevance
“…5 From a clinical perspective, this results in significant advantages of combined ACLR and anterolateral ligament (ALL) reconstruction (ALLR), including reduced graft rupture rates, a lower risk of reoperation for secondary meniscectomy (after meniscal repair), improved knee stability, and higher rates of return to preinjury levels of sports. 31 Comparative studies have demonstrated significant advantages 35 in specific populations, including patients with hyperlaxity, 11 patients who have chronic ACL injury, 10 young patients participating in pivoting sports, 37 and patients undergoing revision ACLR. 15 Despite the resurgence in popularity of combined procedures, it is important to highlight that LEAPs were widely abandoned in the 1980s.…”
mentioning
confidence: 99%
“…5 From a clinical perspective, this results in significant advantages of combined ACLR and anterolateral ligament (ALL) reconstruction (ALLR), including reduced graft rupture rates, a lower risk of reoperation for secondary meniscectomy (after meniscal repair), improved knee stability, and higher rates of return to preinjury levels of sports. 31 Comparative studies have demonstrated significant advantages 35 in specific populations, including patients with hyperlaxity, 11 patients who have chronic ACL injury, 10 young patients participating in pivoting sports, 37 and patients undergoing revision ACLR. 15 Despite the resurgence in popularity of combined procedures, it is important to highlight that LEAPs were widely abandoned in the 1980s.…”
mentioning
confidence: 99%
“…An imaging-proven injury to the ALL has not widely been accepted as an indication, partly because the intrinsic healing potential is not well-understood. However, this is certainly an important area for further study because Sobrado et al 39 recently reported that patients with an imaging-proven ALL injury experienced higher ACL graft rupture rates and worse functional outcomes than patients with isolated ACL injuries.…”
mentioning
confidence: 99%
“…Ferretti et al described that in up to 90% of ACL injured knees, additional lesions were found to the lateral structures [ 9 ]. Inferior clinical results were noted by Sobrado et al when comparing patients with ACL reconstructed knees and concomitant, but untreated ALL lesions to patients treated for isolated ACL ruptures with intact lateral structures [ 52 ]. These clinical studies are supported by overwhelming biomechanical data regarding the role of the ALC as a more efficient lever arm to control the rotatory translation when compared to an isolated ACLR [ 11 , 32 , 39 , 56 ].…”
Section: Discussionmentioning
confidence: 99%